2016
DOI: 10.2147/ndt.s99229
|View full text |Cite
|
Sign up to set email alerts
|

Late life bipolar disorder evolving into frontotemporal dementia mimic

Abstract: ObjectivesAlthough bipolar disorder has been understood classically as a cyclic disease with full recovery between mood episodes, in the last decade, evidence has accumulated supporting progressive features. The clinical picture of advanced or end-stage bipolar disorder is heterogeneous with possible deficits in cognition and behavior, as illustrated by our case series.CasesFrom our neuropsychiatric outpatient clinic, we describe four cases with bipolar disorder gradually developing a clinical syndrome, includ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
32
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(35 citation statements)
references
References 35 publications
2
32
0
1
Order By: Relevance
“…Although not always consistent, evidence tends to indicate that older onset patients have a greater incidence of neurological comorbidities and are less likely to have a family history of psychiatric illness, suggesting that different etiological factors may be involved. Relevantly, there are case reports suggesting that early stage neurodegenerative disease can mimic psychosis and BD, such that a late manifestation of BD and associated cognitive impairment may represent a putative prodrome marker from which dementia or Alzheimer's Disease may emerge . Nonetheless, BD patients appear to be at an increased risk of developing pre‐senile and senile dementia compared to those with other psychiatric or medical conditions as well as the general population, irrespective of onset age .…”
Section: Trajectory Of Cognitive Functioning In Bdmentioning
confidence: 99%
See 1 more Smart Citation
“…Although not always consistent, evidence tends to indicate that older onset patients have a greater incidence of neurological comorbidities and are less likely to have a family history of psychiatric illness, suggesting that different etiological factors may be involved. Relevantly, there are case reports suggesting that early stage neurodegenerative disease can mimic psychosis and BD, such that a late manifestation of BD and associated cognitive impairment may represent a putative prodrome marker from which dementia or Alzheimer's Disease may emerge . Nonetheless, BD patients appear to be at an increased risk of developing pre‐senile and senile dementia compared to those with other psychiatric or medical conditions as well as the general population, irrespective of onset age .…”
Section: Trajectory Of Cognitive Functioning In Bdmentioning
confidence: 99%
“…Relevantly, there are case reports suggesting that early stage neurodegenerative disease can mimic psychosis and BD, such that a late manifestation of BD and associated cognitive impairment may represent a putative prodrome marker from which dementia or Alzheimer's Disease may emerge. [52][53][54] Nonetheless, BD patients appear to be at an increased risk of developing pre-senile and senile dementia compared to those with other psychiatric or medical conditions as well as the general population, irrespective of onset age. [55][56][57][58][59] A register-based study of >4200 patients with BD revealed that the long-term risk of dementia increases with the number of manic and depressive mood episodes, with a 6% increased risk for every new episode.…”
Section: Nonetheless It Should Be Noted That Relatively Limited Follmentioning
confidence: 99%
“…After all, their patients had cognitive performances that were regarded as only mildly impaired, had no neuroimaging abnormalities, and did not show cognitive decline during follow-up. It is noteworthy that our group retrospectively studied patients with a similar clinical history to Dols 71 , but in the findings by Gambogi et al 72 , including neuroimaging and cognitive testing, there were only subtle differences in a typical bvFTD patient. Gambogi et al found that the frequency of antipsychotic drug use, primitive reflexes, apathy, stereotypic/compulsive/ritualistic behaviors, and family history of psychosis were statistically higher in bvFTD patients with a prior history of SMI than in patients with typical bvFTD.…”
Section: Neuroprogression Models In Severe Mental Illness and The Neumentioning
confidence: 74%
“…The patient had a novel mutation in the progranulin (GRN) gene on chromosome 17. According to Dols [87] and colleagues, symptoms fitting the criteria for possible bvFTD may be present in the endstage of BD. Meisler and colleagues [88] reported C9ORF72 expansion (it is involved in the processes of intracellular vesicle trafficking) in a family with BD and FTD, highlighting a possible etiological relationship between the C9ORF72 expansion and disease progression from BD to FTD.…”
Section: Frontotemporal Dementia (Ftd)mentioning
confidence: 99%